Biblioterapi sebagai Pengembang Layanan di Perpustakaan Sekolah Luar Biasa Negeri 1 Padang - Agustin, Mairani Tri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract The study of this research in about biblioterapy as a service development in the school library extraordinary number 1 Padang. The purpose is to describe about, development of bibliotherapy services in the country’s extraordinary school library number 1 Padang, obstacles encountered in the development of biblioterapy service school library number 1 Padang, effors made in the development of biblioterapy.This mothod descriptive method. Interviews and extraordinary libraries number 1 Padang.Based on the research it can be concluded that 1 development of biblioterapy service in the extraordinary school library of number 1 padang country, developing biblioterapy service such as student by teacher in library using book. Keywords : biblioterapy, school library.